Optimizing The Role Of Sharia Banking In Supporting Halal Tourism In Indonesia - Adinugroho, Mukhtar; Efendi, Mohamad Nur; Nasrulloh, Nasrulloh; Zuhdi, Ubaidillah (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to analyze the role of sharia banking in supporting halal tourism and to analyze the potential of sharia banks in supporting halal tourism. This type of research is qualitative descriptive research based on the results of interviews and documentation. The results of the research show that the condition of sharia banks in supporting halal tourism has not carried out effective outreach to tourism industry players, access to offices and ATM networks is still difficult to find and there is a lack of promotion carried out by sharia banks while the potential of sharia banks themselves can carry out product innovation by providing specific financing products for tourism industry players and holding interesting events to change the public mindset that Islamic banks are inclusive and not exclusive banks.